2020
DOI: 10.1186/s42787-019-0057-2
|View full text |Cite
|
Sign up to set email alerts
|

MHD slip flow of upper-convected Maxwell nanofluid over a stretching sheet with chemical reaction

Abstract: The present study scrutinizes slip effects and stagnation point flows of upperconvected Maxwell fluid past a stretching sheet. The non-linear ordinary differential equations are obtained from the governing partial differential equations and solved using implicit finite difference method. The impacts of non-dimensional governing parameters such as Brownian motion parameter, velocity ratio, velocity slip parameter, suction/injection parameter, Lewis numbers, upper-convected Maxwell parameter, magnetic field, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(34 citation statements)
references
References 42 publications
0
34
0
Order By: Relevance
“…Koriko et al [8] analyzed the conduct of thermal stratification and nonlinear thermal radiation on micropolar fluid moving over a vertical surface. e phenomenon of heat transfer has been investigated by many researchers [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Koriko et al [8] analyzed the conduct of thermal stratification and nonlinear thermal radiation on micropolar fluid moving over a vertical surface. e phenomenon of heat transfer has been investigated by many researchers [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Barik et al 5 examined the chemically reactive nanofluid past an inclined elongated sheet with slip conditions. Ibrahim and Negera 6 investigated the upper‐convected Maxwell nanoliquid with chemical reaction. Rehman et al 7 studied the heat transfer analysis of Casson nanofluid in a magnetized rotatory flow field and found that Casson fluid temperature enhances toward higher values of thermophoresis and heat generation parameters.…”
Section: Introductionmentioning
confidence: 99%
“…They also found that the rate of heat transfer declined as there was increase in the heat generation/absorption values. Similarly, in several other studies, the characteristic of heat transfer was analyzed due to the fluid flow over stretching sheet [18][19][20]. Ganga et al [21] explored viscous and Ohmic dissipation effects on MHD flow subjected to an upright plate in addition to heat generation/absorption effect on nanofluid.…”
Section: Introductionmentioning
confidence: 99%